IOT devices based improved cryptosystem for secure image sharing - Budida Harikranth, Venkatakrishna Adla, Lingamaiah Malle, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The security and integrity of medical data have become major problems for healthcare services applications due to the considerable growth of the internet of things (IoT) in the healthcare industry. For protecting diagnostic text data in medical pictures, this study offers a hybrid security architecture. The suggested model is created by combining a proposed hybrid encryption method with either 2D-Discrete Wavelet Transform 1 Level (2D-DWT-1L) or 2D-DWT-2L steganography. The Advanced Encryption Standard (AES) and Rivest, Shamir, and Adleman (RSA) algorithms are combined in the proposed hybrid encryption scheme. The Advanced Encryption Standard (AES) and Rivest, Shamir, and Adleman (RSA) algorithms are combined in the proposed hybrid encryption scheme. The suggested methodology encrypts the secret data first, then uses 2D-DWT-1L or 2D-DWT-2L to conceal the result in a cover picture. To hide varying text sizes, cover pictures in both colour and grayscale are utilized. The results of the experiments demonstrate that the suggested picture steganography approach achieves a reasonable balance of resilience and invisibility, even for messages of various sizes.